Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M190 - Wolfgang Bach; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M190 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 2023-06-08 – 2023-07-08 from Las Palmas (Gran Canaria) to Algeciras (Spain) in the Central Atlantic Ocean. The main objective of M190 was highly coordinated sampling of fluids, rocks, and biota as part of the joint geo-bio interface studies in the Research Area extquotesingleOcean Floor as a Reactor extquotesingle of the proposed Cluster of Excellence The Ocean Floor – Earth extquotesingles Uncharted Interface. Data were recorded in the Portuguese EEZ around the Azores and Madeira. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.